Price and Product Quality as Determinants of Purchasing Decisions: A Case Study on Mrs. Ida’s Potato Chips - Muhammad Akbar Al-Asyari; Asri Solihat; Lindayani . (Jurnal Inovasi Bisnis dan Kewirausahaan, 2025)
This study aims to find out and analyze the influence of price and product quality on consumer purchase decisions of "Ibu Ida Potato Chips". Data were collected by questionnaire distribution technique using a Likert scale. The population in this study is Mrs. Ida's potato chips consumers who have purchased potato chips in Garut Regency. The sample was selected using accidental sampling and a sample of 100 respondents was obtained using the zikmund formula. In this study, it uses classical assumption tests, multiple linear analysis, and hypothesis tests. The hypothesis testing consists of a t-test, an f-test, and a coefficient of determination. The results of the study showed that there was an influence of price variables and product quality on purchase decision variables of 31.9% while the remaining 68.1% was influenced by other variables that were not studied in this study. When viewed individually, the price variable has an effect of 0.257 or 25.7% on the purchase decision. Meanwhile, the product quality variable has an effect of 0.239 or 23.9% on the purchase decision.